2014
DOI: 10.1371/journal.pone.0099111
|View full text |Cite
|
Sign up to set email alerts
|

Choosing Important Health Outcomes for Comparative Effectiveness Research: A Systematic Review

Abstract: BackgroundA core outcome set (COS) is a standardised set of outcomes which should be measured and reported, as a minimum, in all effectiveness trials for a specific health area. This will allow results of studies to be compared, contrasted and combined as appropriate, as well as ensuring that all trials contribute usable information. The COMET (Core Outcome Measures for Effectiveness Trials) Initiative aims to support the development, reporting and adoption of COS. Central to this is a publically accessible on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
298
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 279 publications
(302 citation statements)
references
References 12 publications
4
298
0
Order By: Relevance
“…Moreover, findings of this study emphasise the importance of patient and family input to decision making regarding core outcome domains, which has been under-represented in prior projects aimed at creating core outcome sets 44. Incorporating patient perspectives is important to ensure that the outcomes measured by researchers are patient centred 45 46.…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, findings of this study emphasise the importance of patient and family input to decision making regarding core outcome domains, which has been under-represented in prior projects aimed at creating core outcome sets 44. Incorporating patient perspectives is important to ensure that the outcomes measured by researchers are patient centred 45 46.…”
Section: Discussionmentioning
confidence: 98%
“…These include primary qualitative research—in-depth interviews or focus groups15—undertaken for the purpose of the Core Outcome Set, and systematic reviews of published qualitative research 16. Such approaches are required because clinical trials have been repeatedly shown to miss outcomes considered important by these other stakeholder groups 17 18…”
Section: Identifying a Core Outcome Setmentioning
confidence: 99%
“…Different techniques have been used to reach consensus regarding which outcomes are ‘core.’ These range from relatively informal methods, such as semistructured group discussion at a workshop or meeting, to more formal group work, such as use of the Nominal Group technique 15. Currently the most common method used is modified Delphi technique13 ; this allows the views of a large number of geographically diverse stakeholders to be integrated quickly and efficiently.…”
Section: Identifying a Core Outcome Setmentioning
confidence: 99%
“…1e3 At present, there is a growing interest for the inclusion of HRQL assessment in clinical trials in Oncology, allowing for comparison, contrast, or combining as appropriate, in order to ensure the production of high-quality evidence. 3 Recent reports have evaluated the association of HRQL and prognosis in cancer, 4,5 and specifically in Head and Neck (H&N) squamous cell carcinoma. 6,7 However, there is scarce information that explores improvement in HRQL as a result of adequate treatments in the prognosis of H&N cancers, although this interesting association has been reported in other neoplasms.…”
Section: Introductionmentioning
confidence: 99%